Combination of budesonide/formoterol more effective than fluticasone/salmeterol in preventing exacerbations in chronic obstructive pulmonary disease: the PATHOS study. (1st April 2013) - Larsson, K.; Janson, C.; Lisspers, K.; Jørgensen, L.; Stratelis, G.; Telg, G.; Ställberg, B.; Johansson, G.
Abstract Objectives Combinations of inhaled corticosteroids (ICSs) and long‐acting β2‐agonists (LABAs) are recommended for patients with moderate and severe chronic obstructive pulmonary disease (COPD). However, it is not known whether different fixed combinations are equally effective. The aim of this study was to investigate exacerbation rates in primary care patients with COPD treated with budesonide/formoterol compared with fluticasone/salmeterol. Methods Patients with physician‐diagnosed COPD and a record of postdiagnosis treatment with a fixed combination of budesonide/formoterol or fluticasone/salmeterol were included. Data from primary care medical records were linked to those from Swedish national hospital, drug and cause of death registers. Pairwise (1 : 1) propensity score matching was carried out at the index date (first prescription) by prescribed fixed ICS/LABA combination. Exacerbations were defined as hospitalizations, emergency visits and collection of oral steroids or antibiotics for COPD. Yearly event rates were compared using Poisson regression. Results Matching of 9893 patients (7155 budesonide/formoterol and 2738 fluticasone/salmeterol) yielded two cohorts of 2734 patients, comprising 19 170 patient‐years. The exacerbation rates were 0.80 and 1.09 per patient‐year in the budesonide/formoterol and fluticasone/salmeterol groups, respectively (difference of 26.6%; P < 0.0001); yearly rates for COPD‐related hospitalizations were 0.15 and 0.21, respectively (difference of 29.1%; P < 0.0001). All other healthcare outcomes were also significantly reduced with budesonide/formoterol versus fluticasone/salmeterol. Conclusions Long‐term treatment with fixed combination budesonide/formoterol was associated with fewer healthcare utilization‐defined exacerbations than fluticasone/salmeterol in patients with moderate and severe COPD.